PENURUNAN PRODUKTIVITAS PURSE SEINE DI PELABUHAN PERIKANAN PANTAI PULAU BAAI BENGKULU - Maman Hermawan; Eli Nurlaela (Politeknik Ahli Usaha Perikanan, 2023)
Pulau Baai Beach Fisheries Port is the center of fishery economic growth and development in the city of Bengkulu, which is based on capture fisheries. The development of fishing business in fishing ports is a form of the development of capture fisheries activities in a port, which development defines more advanced fishing business activities. Productivity is one way to see the ability of fishing units to produce fish caught. The productivity of purse seine vessels is an important indicator to see how the production conditions produced by these fishing gears. This research was conducted at the Pulau Baai Beach Fishing Port, with the time for conducting the research starting from March 21 to May 30, 2022. The results showed that the productivity per trip of purse seine vessels has decreased in the last three years, where the productivity decrease was significantly by 35% occurred in 2019-2021, while in 2019-2020 the decline in productivity was 2.65 tonnes/trip, or 13.5%. Meanwhile, productivity based on the average GT of ships has exceeded the established standards.